The effects of informal settlements on environmental management in Temeke Municipality - Mwamhanga, Evaristo Benitho (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Environmental Management (MSc. EM) of Mzumbe University